Analysis of the Quality of Health Center Services Based on Public Service Regulation by the Government - Ambo Dalle; Sri Purwantono; Bahtiar Bahtiar (Humanistic Network for Science and Technology (HNST), 2020)
Health centers are expected to provide quality health services that meet the needs of the customers. Health centers need to improve services in order to be able to compete, develop, and grow. This study describe the satisfaction of the customers for services provided by Kendal Health Center, Ngawi, Indonesia. The population of this study were community who utilized health services at the Kendal Health Center in 2016. The sample were selected using quota sampling. Each unit of service given a quota of 20 respondents, while auxiliary health center were quota of 10 respondents, because the customer visit at a auxiliary health center were lower. The variable was the satisfaction with services provided by health center. Data were collected by filling out questionnaires, then analyzed descriptively using spiderweb diagram. In general, the results of the study indicate that the quality of health center services was in the good category, and all service units had succeeded in exceeding the predetermined targets. Keywords: health center; service quality; public service